Impaired sperm function in infertile men relies on the membrane sterol pattern. (29th January 2018) - Garolla, A.; Šabović, I.; Tescari, S.; De Toni, L.; Menegazzo, M.; Cosci, I.; De Filippis, V.; Giarola, M.; Foresta, C.
Summary: Membrane cholesterol removal appears a key step for the gain of fertility potential during sperm maturation. However, the membrane sterol pattern in sperm cells from infertile patients, with impaired sperm parameters, has been poorly investigated. To elucidate a causative link between sperm membrane composition in male fertility, here we have investigated the levels of cholesterol and its oxidized derivatives 7β‐hydroxycholesterol and 7‐keto‐cholesterol in sixteen infertile patients with oligo‐asthenozoospermia and 16 normozoospermic (N) fertile subjects. Furthermore, ten of 16 N fertile subjects agreed to receive a defined testicular thermal challenge by adhering to a programme of sauna sessions for 1 month. Semen samples were obtained from each of the participants, and sperm parameters were assessed according to the World Health Organization criteria. Sperm levels of cholesterol, 7β‐hydroxycholesterol and 7‐keto‐cholesterol were quantified by ultra‐pressure liquid chromatography mass spectrometry. The results showed that oligo‐asthenozoospermia patients had a huge amount of cholesterol content compared with fertile subjects (12.40 ± 6.05 μg/10 6 cells vs. 0.45 ± 0.28 μg/10 6 cells, p  < 0.001, N and oligo‐asthenozoospermia, respectively). Also, oxidized derivatives were significantly higher in oligo‐asthenozoospermia patients (7β‐hydroxycholesterol: 1.96 ± 1.03 ng/10 6 cells vs. 0.075 ± 0.05 ng/10 6 cells, p  < 0.001 and 7‐keto‐cholesterol: 1.11 ± 0.72 ng/10 6 cells vs. 0.005 ± 0.003 ng/10 6 cells, p  < 0.001). Moreover, sauna exposure, in parallel with a progressive worsening of sperm motility parameters, was associated with a reversible increase in sperm cholesterol after the third and fourth week of treatment, whilst 7β‐hydroxycholesterol and 7‐keto‐cholesterol levels showed an earlier enhancement starting from the second week. Our data show for the first time in humans a strong difference in the cholesterol and its oxidized derivatives of infertile and fertile subjects. These findings suggest a strict biochemical link relating testis function, sperm membrane status and male fertility potential.